Strategic control of the cattle tick Rhipicephlaus microplus applied to rotational and silvopastoral grazing systems in subtropical areas - Nava, Santiago; Rossner, Maria Victoria; Toffaletti, Jose Rodolfo; Da Luz, Miguel; Rossner, Maria Belen; Signorini Porchiett, Marcelo Lisandro; Morel, Nicolas (Springer Link, 2024)
This work evaluated if strategic control based on no more than three or four annual treatments is useful to control Rhipicephalus microplus infestations on cattle when it is applied to intensive rotational grazing and silvopastoral systems with high stocking rates in subtropical areas. In the intensive rotational grazing system, three annual treatments with chemical acaricides were applied on cattle in two different schemes: between spring and early summer and from late winter and late spring. Strategic control based on three treatments with chemical acaricides from late winter to late spring plus an additional fourth treatment in summer was tested in the silvopastoral system. In the intensive rotational grazing systems, the control schemes allow to reach a significant reduction in the tick load on cattle considering a time interval from spring to autumn. However, the efficacy levels were not high enough in some specific moments, namely, the tick counts of summer and autumn (there were not significant differences between treated and control groups). The scheme evaluated in the silvopastoral grazing system yielded better results than those tested for the intensive rotational system, because significant differences in tick load between treated and control groups were observed in all post-treatment counts and when the analysis was performed for the whole study period. However, values of efficacy in the count-by-count comparison were disparate, ranging from 64.1 to 99.7. Although the efficacy values obtained in the silvopastoral system were better than those of the rotational grazing systems, the total tick load on treated cattle in autumn was not low enough (mean abundance values 25.14 and 38.14). Ticks were more evenly distributed among hosts in late summer and autumn than in spring or early summer, where few hosts carry most of the ticks. Some management strategies as intensive rotational systems or silvopastoral structures can lead to a more efficient forage use, but they imply greater tick challenge than in extensive grazing systems. In these situations, the schemes of strategic control bases on three or four annual treatments should be complemented with additional tactical treatments in late summer or autumn.